The Role of Industry in Satellite Towns of Polish and French Metropolitan Areas – Case Study of Myślenice and Issoire - Kwiatek-Sołtys, Agnieszka; Wiedermann, Krzysztof; Mainet, Helene; Edouard, Jean-Charles (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The emerging problem of changing and shrinking economic base of many small towns causes necessity of searching for new paths of development for them. Former central service functions existing in many small towns are largely washed out to larger cities as a result of the present metropolisation processes. The question arises to what extent these towns are or may be attractive for the development of production functions.The aim of the paper is to show the role of industry for the development of small towns in Małopolska in Poland and Auvergne in France on the case studies of Myślenice and Issoire.